Stereotactic Body Radiation Therapy for Prostate Cancer: What is the Appropriate Patient-Reported Outcome for Clinical Trial Design? - Woo, Jennifer Ai-Lian; Chen, Leonard N.; Wang, Hongkun; Cyr, Robyn A.; Bhattasali, Onita; Kim, Joy S.; Moures, Rudy; Yung, Thomas M.; Lei, Siyuan; Collins, Brian Timothy; Suy, Simeng; Dritschilo, Anatoly; et al. (Frontiers in Oncology, 2015)
Purpose: Stereotactic body radiation therapy (SBRT) is increasingly utilized as primary treatment for clinically localized prostate cancer. Consensus regarding the appropriate patient-reported outcome (PRO) endpoints for clinical trials for early stage prostate cancer RT is lacking. To aid in trial design, this study presents PROs over 36 months following SBRT for clinically localized prostate cancer. Methods: 174 hormone-naïve patients were treated with 35-36.25 Gy SBRT in 5 fractions. Patients completed the EPIC-26 questionnaire at baseline and all follow-ups; the proportion of patients developing a clinically significant decline in each EPIC domain was determined. The minimally important difference (MID) was defined as a change of one-half SD from the baseline. Per RTOG 0938, we examined the percentage of patients who reported decline in EPIC urinary summary score of >2 points and EPIC bowel summary score of >5 points from baseline to one year. Results: 174 patients received SBRT with minimum follow-up of 36 months. The proportion of patients reporting a clinically significant decline in EPIC urinary/bowel scores was 34%/30%, 40%/32.2%, and 32.8%/21.5% at 6, 12, and 36 months. The percentage of patients reporting decline in the EPIC urinary summary score of >2 points was 43.2%, 51.6% and 41.8% at 6, 12, and 36 months. The percentage of patients reporting decline in EPIC bowel domain summary score of >5 points was 29.6% 29% and 22.4% at 6, 12, and 36 months. Conclusion: Our treatment protocol meets the RTOG 0938 criteria for advancing to a Phase III trial compared to conventionally fractionated RT. Between 12-36 months, the proportion of patients reporting decrease in both EPIC urinary and bowel scores declined, suggesting late improvement in these domains. Further investigation is needed to elucidate 1) which domains bear the greatest influence on post-treatment QOL, and 2) at what time point PRO endpoint(s) should be assessed.